Live wire : long-winded short stories [large type] - Ripa, Kelly (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
"A sharp, funny, and honest collection of real-life stories from Kelly Ripa, showing the many dimensions and crackling wit of the beloved daytime talk show host"--